Prediction of cutting forces developed during hard turning of hard chrome plated surfaces on EN24 substrate / K. N. Mohandas, C. S. Ramesh and Eshwara Prasad Koorapati - K. N. Mohandas; C. S. Ramesh; Eshwara Prasad Koorapati (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2013)
This paper investigates the development of cutting forces during the hard turning of hard chrome plated surfaces on EN24 substrate. The hard turning operation disproves the Merchant's theory of cutting force development during the machining as the hard turning is only a small stock material removal. Various forces produced such as cutting force, feed force and thrust force have been measured during the finish turning. The experimental results have indicated that the feed force is the predominant force out of three different forces developed. This is in good agreement with the available literature. The results obtained from the experimentation were used to predict the optimum cutting conditions in terms of cutting forces. The optimized cutting parameters are feed of 0.08mm/rev, cutting speed of 500rpm and depth of cut of 40jum. The developed mathematical model exhibited satisfactory goodness of the model fit in regression with different PcBN cutting tool inserts. A maximum of 5% variation in the experimental results of the cutting forces when compared with the mathematical model has been observed. This suggests that the developed mathematical model could be employed to predict the cutting forces during hard turning of hard chrome plated surfaces.